Treatment of canine and feline sarcoma using MR-guided focused ultrasound system - Antoniou, Anastasia; Evripidou, Nikolas; Panayiotou, Stelios; Spanoudes, Kyriakos; Damianou, Christakis A. (My University, 2022)
In recent years, veterinary medicine has enhanced its applications beyond traditional approaches, progressively incorporating the Focused Ultrasound (FUS) technology. This study investigated the ability of FUS to precisely ablate naturally occurring canine and feline soft tissue sarcomas (STS).
Keywords: Cats; Dogs; MRgFUS; Robotic device; Sarcomas; Superficial cancer